Corals as Chemical Archives: PAH Concentration, Transformation, and Ecosystem Risk Across the Tropical Belt - Halikuddin Umasangaji; Yunita Ramili; Nur Afifa Asyiqin; Lilik Maslukah (Universitas Diponegoro, 2026)
Polycyclic aromatic hydrocarbons (PAHs) are now widespread and consequential contaminants in tropical and subtropical coral reef ecosystems. Studies from the Arabian Sea, South China Sea, Brazilian Atlantic, Persian Gulf, Gulf of Suez, and remote oceanic archipelagos show that PAHs permeate seawater, suspended particulates, sediments, island soils, coral tissues, mucus, Symbiodiniaceae, benthic invertebrates, and reef fishes. Although many concentrations fall within regulatory categories labeled low to moderate, experimental and field data reveal physiological impairment, bioaccumulation, trophic transfer, and metabolic stress at levels below existing environmental thresholds. Multi-matrix comparisons demonstrate large heterogeneity, with particulates and biological tissues showing orders-of-magnitude enrichment over dissolved fractions. Extreme particulate loads reported from Lakshadweep lagoons (6469.86 ng g⁻¹) and high concentrations in Persian Gulf coral tissues (1127 ng g⁻¹) and zooxanthellae (1421 ng g⁻¹) indicate that corals and symbionts act as biochemical concentrators. Atmospheric deposition, including gas-phase PAHs up to 113.1 ng m⁻³ in offshore South China Sea reefs, highlights long-range transport independent of local industry. Experimental research also shows sensitivity in early life stages and symbioses, including coral-larval impairment at 34 µgTAHL⁻¹ and fossil-carbon assimilation by Symbiodiniaceae under crude-oil exposure. Briefly, PAHs represent chronic ecosystem-level stressors with major implications for coral-reef resilience under accelerating climate pressure.